Expanding donor availability in lung transplantation: A case report of 5000 miles traveled. Issue 6 (27th April 2021) - Fitch, Zachary W.; Doberne, Julie; Reynolds, John M.; Jamieson, Ian; Haney, John C.; Klapper, Jacob A.; Hartwig, Matthew G.
Abstract: We present the case of a 41‐year‐old female who underwent bilateral lung transplantation after the donor lungs were placed on a normothermic ex vivo lung perfusion and ventilation device and flown nearly 5000 miles from Honolulu, Hawaii to Durham, North Carolina. The patient experienced no primary graft dysfunction. One year after transplantation she has remained rejection‐free and exhibits excellent pulmonary function. This case highlights the challenge that active organ preservation systems pose to questions of organ allocation and geographic sharing. Abstract : Successful transplantation of donor lungs flown nearly 5, 000 miles using an ex vivo lung perfusion and ventilation system challenges premises of lung allocation and geographic sharing.